Penanggulangan Abrasi Pantai Di Desa Galesong Dengan Menggunakan Metode Seawall - Putra, Muhammad Kinantang (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Environmental damage that generally occurs is coastal abrasion. This problem must be addressed immediately because it can result in enormous losses for living things and ecosystems. Abrasion is the erosion or reduction of land (coast) due to wave activity, currents and tides. In this connection, land compaction causes the land surface to drop and be inundated by sea water so that the coastline changes. coastal abrasion langan. The purpose of this study is to find out how much coastal wave deformation occurs in Galesong Village and find out how countermeasures can be done to prevent abrasion in Galesong Village. Countermeasures that can be done in Galesong village are by using the seawall method. With the wave deformation of Galesong beach as follows, The wave height of the plan is 1.89 m, The wave height breaks 1.10 m, The wave depth breaks 1.60 m, and The wave period is 10 seconds.